Sulfide removal using ozone as an oxidizing agent in tannery wastewater (2019)
In this study, the removal of sulfides in wastewater from the process of peeling or depilating skins was evaluated, using ozone as an oxidizing agent. The effect of the initial pH on the removal process was determined, for this purpose a completely randomized experimental design was used, in which the pH of the water was varied between 10, 11, 12 and 13, the ozone was dosed at a rate 0.5 g h-1 for a period of 3 hours taking samples every 30 minutes. The tests were performed for the real wastewater, supplied by a tannery and synthetic wastewater, in order to compare the removal achieved in each case. The analysis of the results obtained showed that the highest removal was achieved at pH 11 in the actual wastewater, reaching a value of 77.78%, approximately 39% higher than that reached at the same pH for the synthetic wastewater. The kinetics of the process were also evaluated, obtaining that the results are adjusted to a kinetic of pseudo first order for which the kinetic coefficient was -0,0001 s-1, finally, it was observed that after each test there was a decrease pH, which confirms what chemically should happen, formation of H2SO4 by the oxidation of sulphides to sulfates. Finally, it is concluded that the removal of sulfides using ozone is a technique applicable for alkaline pH, allowing to reduce oxidation times and becoming a viable alternative to apply in the leather tanning industry.